A Brief Overview to Some Words in The Book of Dedem Korkut Through the Line of Language and Culture - (:unkn) unknown (MILLI FOLKLOR DERGISI, 2015)
Although a great many studies were conducted on it, The Book of Dedem Korkut has still many elaborate details, most of which maybe have not been uncovered, yet. These tenuous particularities are hidden under various layers, which can be perceived or figured out only when traced well enough. Such texts juxtaposed with language studies and cultural researches expand with new cultural harbors reached at as the words are chased, so to speak. Hence the voyage drags on and on. Repetition of these. voyages enable the new explorations, which may mean searching the true place of the literary material in the historical maturation of the social interactions through digging the text by means of etymology, in one respect. The misconception that the literary texts could be analyzed by dint of linguistics can only be razed through such studies. On the other hand, by way of multilayered texts posed as identity of national heritage such as The Book of Dedem Korkut, the depth of the language workmanship increases or the true value of the language researches is well understood. Thus, it is clearly seen that a research procedure quasi today's interdisciplinary one actually has long existed in all of the scientific studies since that time. By no means, an adequate study can be done on such texts such as The Book of Dedem Korkut because of the fact that each single study stirs another opinion in every single person or puts another brick in the wall. The Book of Dedem Korkut was published by Kilisli Muallim Rifat for the first time in 1916 and since then it has been republished again and again, so a great many discoveries have been done in the text. Orhan Saik GOKYAY, Muharrem Ergin, Saadettin Ozcelik and Semih Tezcan are only some of these explorers. Today, the studies carried on The Book of Dedem Korkut still go on. As it is the 200th anniversary of start of the studies, in this study we will also discuss about The Book of Dedem Korkut. In this study, some words thought to be helpful in determining the depths of meaning and layers of the culture in the text will be analyzed in line with linguistic and cultural aspects.
Keywords: The Book of Dedem Korkut; word analysis; culture; language; linguistic research